2019
DOI: 10.1002/jcb.29012
|View full text |Cite
|
Sign up to set email alerts
|

Polydatin enhances the chemosensitivity of osteosarcoma cells to paclitaxel

Abstract: Despite improvements in the prognosis of osteosarcoma patients, chemotherapy fails in a considerable number of cases due to drug resistance. The development of novel agents may enhance chemosensitivity. This study explored the anticancer function of polydatin and its ability—in combination with paclitaxel—to overcome drug resistance in human osteosarcoma U‐2OS and MG‐63 cell lines. A cell proliferation assay (celll counting kit‐8), a cell‐cycle assay, an apoptosis assay (annexin V‐fluorescein isothiocyanate/pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Titanium dioxide (TiO 2 ) nanoparticles are potential materials in the prevention of osteosarcoma and chondrosarcoma recurrence (4). Paclitaxel, classified as a "plant alkaloid, " is isolated originally from the bark of Taxus brevifolia and has been widely reported in the treatment of osteosarcoma (5,6). TiO 2 -embedded paclitaxel nanoparticles have been tried in the prevention of cancer risk (7).…”
Section: Introductionmentioning
confidence: 99%
“…Titanium dioxide (TiO 2 ) nanoparticles are potential materials in the prevention of osteosarcoma and chondrosarcoma recurrence (4). Paclitaxel, classified as a "plant alkaloid, " is isolated originally from the bark of Taxus brevifolia and has been widely reported in the treatment of osteosarcoma (5,6). TiO 2 -embedded paclitaxel nanoparticles have been tried in the prevention of cancer risk (7).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, through the STAT3 signaling pathway, polydatin activates autophagy and leads to apoptosis in MG-63 human osteosarcoma cells [ 12 ]. Interestingly, it has been reported that polydatin reinforces the sensitivity to chemotherapy with paclitaxel in osteosarcoma cells [ 13 ]. However, whether polydatin can overcome drug resistance against the standard anticancer 5-FU drug, and the fundamental mode of action of this process, have not been elucidated yet.…”
Section: Introductionmentioning
confidence: 99%
“…In our precedent paper, we demonstrated that PD was able to induce cell cycle arrest in the S phase, redistributed β-catenin protein, and enhanced osteoblast differentiation markers, including phosphatase alkalin activity, osteopontin, and Notch2 [17]. In addition, polydatin overcomes resistance to paclitaxel in human OS cell lines [34,35]. Published reports suggest that the use of poly (epsiloncaprolactone) complexed with a variety of natural molecules or polymers enhances its biocompatibility and/or its therapeutic action for bone repair.…”
Section: Discussionmentioning
confidence: 82%